Sandwich multilayer high-entropy lead-free dielectric material and preparation method thereof
By using sandwich multi-layer structure and oscillation pressure sintering method in multi-layer ceramic materials, Ba0.2Sr0.2Na0.2Bi0.2Ca0.2Ti0.25Nb0.25Zr0.25Mg0.25O3 with high density and high breakdown field strength was prepared. High-entropy dielectric ceramic materials solve the problems of poor density and low energy storage performance of existing ceramic materials, and achieve high-efficiency energy storage and good temperature stability.
Patent Information
- Application Number
- CN202411646319.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
The existing multi-layer ceramic materials have poor density and low breakdown field strength during sintering, resulting in low energy storage performance and cannot meet the requirements of high-tech weapons for small size and light weight.
Using a sandwich multi-layer structure, Ba0.2Sr0.2Na0.2Bi0.2Ca0.2Ti0.25Nb0.25Zr0.25Mg0.25O3 high-entropy dielectric ceramic layer and Mg2SiO4 dielectric layer were prepared by hydrothermal method and casting method, combined with oscillation pressure sintering method , improve the density of the material and the breakdown field strength.
It has achieved high density, breakdown field resistance up to 1200kV/cm and maximum energy storage density up to 6J/cm3, with good temperature stability and discharge efficiency, and is suitable for energy storage dielectric materials for high-tech weapons.
Smart Images

Figure CN119462080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage ceramics, and in particular relates to a multilayer high entropy dielectric material. Background Art
[0002] As the core energy storage device of high-power pulse power supply, dielectric capacitor has the characteristics of fast charging and discharging speed, high power density and ultra-high power amplification. With the rapid development of pulse power electronic system, pulse power system has put forward higher requirements on the energy storage density, discharge current and time of dielectric capacitor. Since the energy storage density of dielectric capacitor is generally less than 2J / cm 3 ) also makes the pulse power system too large and bulky, unable to meet the requirements of the actual equipment platform for high-tech weapons to be small in size and light in weight. Therefore, driven by the development of advanced pulse power technology and the technical background of equipment miniaturization and lightweight, the development of high energy storage density dielectric capacitors has become an important and urgent research topic.
[0003] The energy storage density is closely related to the dielectric properties and breakdown field strength of the material. Although the current dielectric ceramic materials have a high dielectric constant, the breakdown field strength is low, which seriously restricts the widespread application of dielectric ceramic materials. There is an urgent need to find a method that can simultaneously improve the dielectric constant, breakdown strength and reduce dielectric loss. The use of a multilayer structure can improve the dielectric properties and breakdown resistance of the material because it can combine the advantages of different layers. In particular, the multilayer structure can also adjust the internal electric field distribution and suppress the breakdown path, thereby increasing the breakdown strength, suppressing the dielectric loss, and obtaining a higher energy density. For example, patent publication number CN 108623301A discloses a lead-free, low dielectric loss and high energy storage density ceramic with a sandwich structure and a preparation method thereof. The organic solvent and the emulsifier are mixed evenly, and then SrTiO3 powder, a binder, a dispersant and a plasticizer are added and mixed evenly to obtain a SrTiO3 tape casting slurry; the same tape casting method is used to obtain (1-x)SrTiO3-xBaFe 0.5 Nb 0.5 O3 tape-casting slurry; tape-cast the two tape-casting slurries respectively by tape-casting to obtain two tape-casting films; then stack, pressurize, debind and sinter. Although stacking a wide bandgap, high breakdown field strength dielectric layer and a high entropy dielectric ceramic layer to construct a heterogeneous multilayer film is an effective strategy to reduce leakage current and increase breakdown field strength. However, on the one hand, the introduction of the non-ferroelectric layer significantly weakens its polarization characteristics. How to maintain the dielectric properties of the material while obtaining a high breakdown field strength is a difficulty in related research; on the other hand, the multilayer material has the problem of loose sintering and difficulty in densification. Summary of the invention
[0004] Aiming at the technical problems of non-dense sintering, low breakdown field strength and low energy storage performance of multilayer ceramics, the present invention proposes a sandwich multilayer high entropy lead-free dielectric material and a preparation method thereof. The prepared sandwich multilayer high entropy lead-free dielectric material has high density, high breakdown field strength and high dielectric properties, energy storage density and good discharge efficiency. The breakdown field strength is 1200kV / cm and the maximum energy storage density is 6J / cm 3 , and has good temperature stability. The method has the advantages of being simple, easy to operate, low cost, convenient and fast, and can be mass-produced.
[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] A sandwich multilayer high entropy lead-free dielectric material, comprising upper and lower dielectric layers and a middle high entropy dielectric ceramic layer; the upper and lower dielectric layers are made of Mg2SiO4, and the high entropy dielectric ceramic layer is made of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3.
[0007] A method for preparing a sandwich multilayer high entropy lead-free dielectric material comprises the following steps:
[0008] (1) Preparation of Ba by hydrothermal method 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3;
[0009] (2) Ba was prepared by the flow-through method. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 tape casting and Mg2SiO4 tape casting;
[0010] (3) will Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The O3 tape casting tape and the Mg2SiO4 tape casting tape are stacked in a sandwich structure and firstly hot pressed to obtain a ceramic thick film green body;
[0011] (4) Sandwich multilayer high entropy lead-free dielectric materials are prepared by oscillating pressure sintering of ceramic thick film green bodies.
[0012] The steps of the hydrothermal method are: weighing raw material powders Ba(OH)2, Sr(OH)2, Na(OH)2, Bi(NO3)3, Ca(NO3)2, TiO2, Nb2O5, ZrO2, and MgO according to the stoichiometric ratio, dispersing and dissolving them in a solvent with an alkaline reagent and a morphology regulator, and then conducting a hydrothermal reaction.
[0013] The mass ratio of the raw material powder, alkaline reagent, morphology control agent and solvent is 1: (1-1.5): (1-1.5): (0.6-0.8), the alkaline reagent is sodium hydroxide; the morphology control agent is sodium citrate, sodium bicarbonate or polyvinyl alcohol; the solvent includes alcohol and water in a mass ratio of 1: (1-1.5).
[0014] The temperature of the hydrothermal reaction is 150-185° C. and the time is 8-20 hours.
[0015] The flow-casting method for preparing Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The steps of O3 tape casting or Mg2SiO4 tape casting are as follows: 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 or Mg2SiO4, an adhesive and a solvent II are mixed and ball-milled to obtain a high entropy medium casting slurry or a Mg2SiO4 casting slurry, which is then cast and dried to obtain the product.
[0016] The Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti0.25 Nb 0.25 Zr 0.25 Mg 0.25 The mass ratio of O3 or Mg2SiO4, adhesive and solvent II is 10:(2-5):(10-35).
[0017] Preferably, Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The mass ratio of O3, adhesive and solvent II is 10:(3-5):(15-25); the mass ratio of Mg2SiO4, adhesive and solvent II is 10:(2-4):(0.4-0.7):(10-30).
[0018] The adhesive is Shenzhou No. III adhesive; the solvent II is anhydrous ethanol and toluene, or ethylene glycol and toluene.
[0019] More preferably, the solvent II comprises anhydrous ethanol and toluene, Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The mass ratio of O3, adhesive, anhydrous ethanol and toluene is 10:(3-5):(0.3-0.5):(15-25); the mass ratio of Mg2SiO4, adhesive, anhydrous ethanol and toluene is 10:(2-4):(0.4-0.7):(10-30).
[0020] The hot pressing temperature is 60-85° C., the pressure is 3-15 MPa, and the hot pressing time is 3-10 min.
[0021] The oscillation pressure sintering method is as follows: placing the hot-pressed ceramic thick film green body into an oscillation pressure sintering furnace, when the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 20MPa, the heating rate in the furnace is 1°C / min, and the temperature is kept for 100-30min; then when the temperature is increased to 900°C, the heating rate in the furnace is 2°C / min, and an oscillation pressure of 25MPa is applied on the basis of the pressure of 20MPa, the oscillation frequency is 1Hz, and the temperature is kept for 20min; then under the same oscillation pressure, heating is continued at a heating rate of 3°C / min to a target temperature of 1000°C, and the temperature is kept for 800min after reaching the target temperature; unloading the oscillation pressure, maintaining a constant pressure of 20MPa, cooling at a cooling rate of 3°C / min, and when the temperature in the furnace is cooled to 500°C, unloading the constant pressure, and the material is taken out after cooling to room temperature with the furnace to obtain a sandwich multilayer high entropy lead-free dielectric material.
[0022] The beneficial effects of the present invention are as follows: a sandwich structure multilayer high entropy lead-free dielectric material is prepared by using a tape casting method combined with an oscillating pressure sintering method, and the densification of the multilayer material is achieved by using oscillating pressure sintering, and the wide bandgap, high breakdown field strength Mg2SiO4 dielectric layer and Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The O3 high entropy dielectric ceramic layers are stacked to construct a sandwich structure heterogeneous multilayer film. This solves the problems of the existing multilayer ceramics that are not densely sintered, have low breakdown field strength, and have low energy storage performance. Compared with the prior art, the sandwich multilayer high entropy lead-free dielectric material prepared by the present invention has higher density, higher breakdown field strength, higher dielectric properties, energy storage density and good discharge efficiency, with a breakdown field strength of 1200kV / cm and a maximum energy storage density of 6J / cm 3 , and has good temperature stability. The method has the advantages of being simple, easy to operate, low cost, convenient and fast, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 The Ba prepared in Examples 1 and 2 0.2 Sr0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 XRD pattern of O3 high entropy dielectric ceramic powder.
[0025] Figure 2 This is a cross-sectional scanning electron microscope image of a sandwich multilayer high entropy lead-free dielectric material prepared in Example 2.
[0026] Figure 3 This is the breakdown field strength test spectrum.
[0027] Figure 4 This is the energy storage density test map. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] A sandwich multilayer high entropy lead-free dielectric material, comprising upper and lower dielectric layers and a middle high entropy dielectric ceramic layer; the upper and lower dielectric layers are made of Mg2SiO4, and the high entropy dielectric ceramic layer is made of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3. The preparation method comprises the following steps:
[0031] (1) Preparation of Ba by hydrothermal method 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25O3 nanopowder, weigh Ba(OH)2, Sr(OH)2, Na(OH)2, Bi(NO3)3, Ca(NO3)2, TiO2, Nb2O5, ZrO2, MgO and other raw materials according to the stoichiometric ratio, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder to the reactor, wherein the mass ratio of raw materials, sodium hydroxide, sodium citrate and solvent is 1:1:1:0.6, and the ratio of alcohol to water is 1:1.2. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 20h, the drying temperature is 50℃, and the drying time is 5h.
[0032] (2) The upper and lower layers and the middle layer casting tape are prepared by the casting method. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.2 5Nb 0.25 Zr 0.25 Mg 0.25 O3 powder, Mg2SiO4, anhydrous ethanol and toluene were mixed, zirconium balls were added and stirred evenly, and then Shenzhou III adhesive was added and stirred continuously to prepare the Mg2SiO4 tape-casting slurry for the upper and lower layers and the Ba2O4 tape-casting slurry for the middle layer. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 high entropy lead-free dielectric casting slurry; Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The mass ratio of O3, Shenzhou III adhesive, anhydrous ethanol and toluene is 10:4:0.4:20; the mass ratio of Mg2SiO4, Shenzhou III adhesive, anhydrous ethanol and toluene is 10:3:0.5:20. The casting slurry prepared in the above steps is cast on a glass plate, and after casting, it is laid flat and allowed to stand until the upper and lower layers of Mg2SiO4 strips and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 After the O3 high entropy dielectric material tape is dried, the corresponding casting tape is obtained. The thickness of the casting tape is 15um. The prepared upper and lower layers of Mg2SiO4 tape and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The O3 high entropy dielectric material tapes are stacked in a sandwich structure and firstly hot pressed to obtain a ceramic thick film green body. The hot pressing temperature is 70°C, the pressure is 10MPa, and the hot pressing time is 20min.
[0033] (3) Preparation of sandwich multilayer high entropy lead-free dielectric materials using oscillating pressure sintering
[0034] The hot-pressed ceramic thick film green body is placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 20MPa, the heating rate in the furnace is 1°C / min, and the temperature is kept for 200min. Subsequently, when the temperature is increased to 900°C, the heating rate in the furnace is 2°C / min, and an oscillating pressure of 25MPa is applied on the basis of the pressure of 20MPa, the oscillation frequency is 1Hz, and the temperature is kept for 20min. Then, under the same oscillating pressure, the heating rate is continued to be 3°C / min to the target temperature of 1000°C, and the temperature is kept for 800min after reaching the target temperature. The oscillating pressure is unloaded, the constant pressure of 20MPa is maintained, and the material is cooled at a cooling rate of 3°C / min. When the temperature in the furnace is cooled to 500°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain a sandwich multilayer high entropy lead-free dielectric material.
[0035] Example 2
[0036] A sandwich multilayer high entropy lead-free dielectric material, comprising upper and lower dielectric layers and a middle high entropy dielectric ceramic layer; the upper and lower dielectric layers are made of Mg2SiO4, and the high entropy dielectric ceramic layer is made of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3. The preparation method comprises the following steps:
[0037] (1) Preparation of Ba by hydrothermal method0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 nanopowder, weigh Ba(OH)2, Sr(OH)2, Na(OH)2, Bi(NO3)3, Ca(NO3)2, TiO2, Nb2O5, ZrO2, MgO and other raw materials according to the stoichiometric ratio, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder to the reactor, wherein the mass ratio of raw materials, sodium hydroxide, sodium citrate and solvent is 1:1.5:1.5:0.8, and the ratio of alcohol to water is 1:1.5. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 185℃, the reaction time is 8h, the drying temperature is 60℃, and the drying time is 5h.
[0038] (2) The upper and lower layers and the middle layer casting tape are prepared by the casting method. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.2 5Nb 0.25 Zr 0.25 Mg 0.25 O3 powder, Mg2SiO4, anhydrous ethanol and toluene were mixed, zirconium balls were added and stirred evenly, and then Shenzhou III adhesive was added and stirred continuously to prepare the Mg2SiO4 tape-casting slurry for the upper and lower layers and the Ba2O4 tape-casting slurry for the middle layer. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 high entropy lead-free dielectric casting slurry; Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25The mass ratio of O3, Shenzhou III adhesive, anhydrous ethanol and toluene is 10:4:0.4:20; the mass ratio of Mg2SiO4, Shenzhou III adhesive, anhydrous ethanol and toluene is 10:3:0.5:20. The casting slurry prepared in the above steps is cast on a glass plate, and after casting, it is laid flat and allowed to stand until the upper and lower layers of Mg2SiO4 strips and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 After the O3 high entropy dielectric material tape is dried, the corresponding casting tape is obtained. The thickness of the casting tape is 15um. The prepared upper and lower layers of Mg2SiO4 tape and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The O3 high entropy dielectric material tapes are stacked in a sandwich structure and firstly hot pressed to obtain a ceramic thick film green body. The hot pressing temperature is 70°C, the pressure is 10MPa, and the hot pressing time is 20min.
[0039] (3) Preparation of sandwich multilayer high entropy lead-free dielectric materials using oscillating pressure sintering
[0040] The hot-pressed ceramic thick film green body is placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 25MPa, the heating rate in the furnace is 3°C / min, and the temperature is kept for 300min. Subsequently, when the temperature is increased to 930°C, the heating rate in the furnace is 5°C / min, and an oscillating pressure of 35MPa is applied on the basis of a pressure of 25MPa, with an oscillation frequency of 3Hz, and the temperature is kept for 30min. Then, under the same oscillating pressure, the temperature is continued to rise at a heating rate of 5°C / min to a target temperature of 1050°C, and the temperature is kept for 60min after reaching the target temperature. The oscillating pressure is unloaded, a constant pressure of 25MPa is maintained, and the material is cooled at a cooling rate of 5°C / min. When the temperature in the furnace is cooled to 550°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain a sandwich multilayer high entropy lead-free dielectric material.
[0041] Example 3
[0042] A sandwich multilayer high entropy lead-free dielectric material, comprising upper and lower dielectric layers and a middle high entropy dielectric ceramic layer; the upper and lower dielectric layers are made of Mg2SiO4, and the high entropy dielectric ceramic layer is made of Ba0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3. The preparation method comprises the following steps:
[0043] (1) Preparation of Ba by hydrothermal method 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 nanopowder, weigh Ba(OH)2, Sr(OH)2, Na(OH)2, Bi(NO3)3, Ca(NO3)2, TiO2, Nb2O5, ZrO2, MgO and other raw materials according to the stoichiometric ratio, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder to the reactor, wherein the mass ratio of raw materials, sodium hydroxide, sodium citrate and solvent is 1:1.2:1.2:0.7, and the ratio of alcohol to water is 1:1.3. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 165℃, the reaction time is 15h, the drying temperature is 55℃, and the drying time is 3h.
[0044] (2) The upper and lower layers and the middle layer casting tape are prepared by the casting method. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.2 5Nb 0.25 Zr 0.25 Mg 0.25 O3 powder, Mg2SiO4, anhydrous ethanol and toluene were mixed, zirconium balls were added and stirred evenly, and then Shenzhou III adhesive was added and stirred continuously to prepare the Mg2SiO4 tape-casting slurry for the upper and lower layers and the Ba2O4 tape-casting slurry for the middle layer. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 high entropy lead-free dielectric casting slurry; Ba0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The mass ratio of O3, Shenzhou III adhesive, anhydrous ethanol and toluene is 10:4:0.4:20; the mass ratio of Mg2SiO4, Shenzhou III adhesive, anhydrous ethanol and toluene is 10:3:0.5:20. The casting slurry prepared in the above steps is cast on a glass plate, and after casting, it is laid flat and allowed to stand until the upper and lower layers of Mg2SiO4 strips and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 After the O3 high entropy dielectric material tape is dried, the corresponding casting tape is obtained. The thickness of the casting tape is 15um. The prepared upper and lower layers of Mg2SiO4 tape and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The O3 high entropy dielectric material tapes are stacked in a sandwich structure and firstly hot pressed to obtain a ceramic thick film green body. The hot pressing temperature is 70°C, the pressure is 10MPa, and the hot pressing time is 20min.
[0045] (3) Preparation of sandwich multilayer high entropy lead-free dielectric materials using oscillating pressure sintering
[0046] The hot-pressed ceramic thick film green body is placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 22MPa, the heating rate in the furnace is 2°C / min, and the temperature is kept for 200min. Subsequently, when the temperature is increased to 910°C, the heating rate in the furnace is 3°C / min, and an oscillating pressure of 26MPa is applied on the basis of the pressure of 22MPa, the oscillation frequency is 2Hz, and the temperature is kept for 25min. Then, under the same oscillating pressure, the heating rate is continued to be 4°C / min to the target temperature of 1020°C, and the temperature is kept for 120min after reaching the target temperature. The oscillating pressure is unloaded, the constant pressure of 23MPa is maintained, and the material is cooled at a cooling rate of 4°C / min. When the temperature in the furnace is cooled to 530°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain a sandwich multilayer high entropy lead-free dielectric material.
[0047] Comparative Example 1
[0048] The difference from Example 1 is that the sintering method in step (3) is different, specifically: the hot-pressed ceramic thick film green body is placed in a sintering furnace, and when the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 22MPa, the heating rate in the furnace is 2°C / min, and the temperature is kept for 200min; then when the temperature is increased to 910°C, the heating rate in the furnace is 3°C / min, and the temperature is kept for 25min; then, the heating is continued to be increased at a heating rate of 4°C / min to a target temperature of 1020°C, and after reaching the target temperature, the temperature is kept for 120min, and the temperature is cooled at a cooling rate of 4°C / min. When the temperature in the furnace is cooled to 530°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain a sandwich multilayer high entropy lead-free dielectric material.
[0049] Figure 1 The Ba prepared in Examples 1 and 2 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The XRD pattern of O3 high entropy dielectric ceramic powder shows that the prepared Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 high entropy dielectric ceramic powder has a good perovskite structure.
[0050] The scanning electron microscope image of the sandwich multilayer high entropy lead-free dielectric material prepared in Example 2 is as follows: Figure 2 As shown, from Figure 2 The final result shows that the thickness of the sandwich multilayer high entropy lead-free dielectric material is 70μm. The upper and lower surfaces of the thick film material are dense Mg2SiO4 dielectric layers, and the middle layer is Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 high entropy dielectric ceramics. From the figure, we can see that the sandwich multilayer high entropy lead-free dielectric material presents a microscopic morphology structure without voids and very dense.
[0051] The samples prepared in Examples 1-3 and Comparative Example 1 were subjected to breakdown field strength test and energy storage density test. Breakdown field strength test conditions: The breakdown strength of the samples was tested using the MS2677-Ⅰ withstand voltage tester of Nanjing Minsheng Company and the test fixture made by the institute. The tester can provide a maximum voltage of 50kV, a leakage current of 5mA, and an electric field application frequency of 200V / s until the sample breaks down, and the voltage value at that time is recorded. In order to prevent discharge in the air during the test, the sample is placed in silicone oil for testing. Usually, a single sample needs to be tested about 10 times.
[0052] Energy storage density test conditions: In order to calculate the energy storage characteristics and withstand voltage characteristics of the composite material, the energy storage density and energy storage efficiency of the sample can be calculated by integrating the hysteresis loop of the sample. The Precision Premier II ferroelectric tester of the American company Radiant Technologies was used to test the hysteresis loop of the polymer composite material. The test details are as follows: at room temperature, the test frequency is 100 Hz, the electric field is applied at 500 kV / cm, and the electric field is gradually increased in steps of 500 kV / cm until the sample breaks down.
[0053] Depend on Figure 3 and 4 It can be seen that by testing its dielectric properties, it is found that the sandwich multilayer high entropy lead-free dielectric material prepared in Example 2 has a breakdown field strength of 1200 kV / cm and a maximum energy storage density of 6 J / cm 3 , and has good temperature stability. The energy storage density of conventional pressure sintering is only 2.2J / cm 3 .
[0054] Example 4
[0055] A sandwich multilayer high entropy lead-free dielectric material, comprising upper and lower dielectric layers and a middle high entropy dielectric ceramic layer; the upper and lower dielectric layers are made of Mg2SiO4, and the high entropy dielectric ceramic layer is made of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3. The preparation method comprises the following steps:
[0056] (1) Preparation of Ba by hydrothermal method 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 nanopowder, weigh Ba(OH)2, Sr(OH)2, Na(OH)2, Bi(NO3)3, Ca(NO3)2, TiO2, Nb2O5, ZrO2, MgO and other raw materials according to the stoichiometric ratio, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder to the reactor, wherein the mass ratio of raw materials, sodium hydroxide, sodium bicarbonate and solvent is 1:1:1:0.6, and the ratio of alcohol to water is 1:1.2. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 20h, the drying temperature is 50℃, and the drying time is 5h.
[0057] (2) The upper and lower layers and the middle layer casting tape are prepared by the casting method. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.2 5Nb 0.25 Zr 0.25 Mg 0.25 O3 powder, Mg2SiO4, ethylene glycol and toluene were mixed, zirconium balls were added and stirred evenly, and then Lecell adhesive was added and stirred continuously to prepare the Mg2SiO4 tape-casting slurry for the upper and lower layers and the Ba2SiO4 tape-casting slurry for the middle layer. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb0.25 Zr 0.25 Mg 0.25 O3 high entropy lead-free dielectric casting slurry; Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The mass ratio of O3, Lecell adhesive, ethylene glycol and toluene is 10:3:0.5:15; the mass ratio of Mg2SiO4, Lecell adhesive, ethylene glycol and toluene is 10:4:0.4:10. The casting slurry prepared in the above steps is cast on a glass plate, and then laid flat and allowed to stand for a while until the upper and lower layers of Mg2SiO4 strips and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 After the O3 high entropy dielectric material tape is dried, the corresponding casting tape is obtained. The thickness of the casting tape is 20um. The prepared upper and lower layers of Mg2SiO4 tape and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The O3 high entropy dielectric material tapes are stacked in a sandwich structure and firstly hot pressed to obtain a ceramic thick film green body. The hot pressing temperature is 60°C, the pressure is 15 MPa, and the hot pressing time is 10 min.
[0058] (3) Preparation of sandwich multilayer high entropy lead-free dielectric materials using oscillating pressure sintering
[0059] The hot-pressed ceramic thick film green body is placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 20MPa, the heating rate in the furnace is 1°C / min, and the temperature is kept for 100min. Subsequently, when the temperature is increased to 900°C, the heating rate in the furnace is 2°C / min, and an oscillating pressure of 25MPa is applied on the basis of the pressure of 20MPa, the oscillation frequency is 1Hz, and the temperature is kept for 20min. Then, under the same oscillating pressure, the heating rate is continued to be 3°C / min to the target temperature of 1000°C, and the temperature is kept for 800min after reaching the target temperature. The oscillating pressure is unloaded, the constant pressure of 20MPa is maintained, and the material is cooled at a cooling rate of 3°C / min. When the temperature in the furnace is cooled to 500°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain a sandwich multilayer high entropy lead-free dielectric material.
[0060] Example 5
[0061] A sandwich multilayer high entropy lead-free dielectric material, comprising upper and lower dielectric layers and a middle high entropy dielectric ceramic layer; the upper and lower dielectric layers are made of Mg2SiO4, and the high entropy dielectric ceramic layer is made of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3. The preparation method comprises the following steps:
[0062] (1) Preparation of Ba by hydrothermal method 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 nanopowder, weigh Ba(OH)2, Sr(OH)2, Na(OH)2, Bi(NO3)3, Ca(NO3)2, TiO2, Nb2O5, ZrO2, MgO and other raw materials according to the stoichiometric ratio, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder to the reactor, wherein the mass ratio of raw materials, sodium hydroxide, sodium citrate and solvent is 1:1:1:0.6, and the ratio of alcohol to water is 1:1.2. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 20h, the drying temperature is 50℃, and the drying time is 5h.
[0063] (2) The upper and lower layers and the middle layer casting tape are prepared by the casting method. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.2 5Nb 0.25 Zr 0.25 Mg 0.25 O3 powder, Mg2SiO4, anhydrous ethanol and toluene were mixed, zirconium balls were added and stirred evenly, and then Shenzhou III adhesive was added and stirred continuously to prepare the Mg2SiO4 tape-casting slurry for the upper and lower layers and the Ba2O4 tape-casting slurry for the middle layer. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 high entropy lead-free dielectric casting slurry; Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The mass ratio of O3, Shenzhou III adhesive, anhydrous ethanol and toluene is 10:5:0.3:25; the mass ratio of Mg2SiO4, Shenzhou III adhesive, anhydrous ethanol and toluene is 10:2:0.7:30. The casting slurry prepared in the above steps is cast on a glass plate, and after casting, it is laid flat and allowed to stand until the upper and lower layers of Mg2SiO4 strips and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 After the O3 high entropy dielectric material tape is dried, the corresponding casting tape is obtained. The thickness of the casting tape is 10um. The prepared upper and lower layers of Mg2SiO4 tape and the middle layer of Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25The O3 high entropy dielectric material tapes are stacked in a sandwich structure and firstly hot pressed to obtain a ceramic thick film green body. The hot pressing temperature is 85°C, the pressure is 3MPa, and the hot pressing time is 3min.
[0064] (3) Preparation of sandwich multilayer high entropy lead-free dielectric materials using oscillating pressure sintering
[0065] The hot-pressed ceramic thick film green body is placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 20MPa, the heating rate in the furnace is 1°C / min, and the temperature is kept for 200min. Subsequently, when the temperature is increased to 900°C, the heating rate in the furnace is 2°C / min, and an oscillating pressure of 25MPa is applied on the basis of the pressure of 20MPa, the oscillation frequency is 1Hz, and the temperature is kept for 20min. Then, under the same oscillating pressure, the heating rate is continued to be 3°C / min to the target temperature of 1000°C, and the temperature is kept for 800min after reaching the target temperature. The oscillating pressure is unloaded, the constant pressure of 20MPa is maintained, and the material is cooled at a cooling rate of 3°C / min. When the temperature in the furnace is cooled to 500°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain a sandwich multilayer high entropy lead-free dielectric material.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A sandwich multilayer high entropy lead-free dielectric material, characterized in that: It includes upper and lower dielectric layers and a middle high entropy dielectric ceramic layer; the materials of the upper and lower dielectric layers are both Mg2SiO4, and the material of the high entropy dielectric ceramic layer is Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3.
2. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 1, characterized in that: The following steps are involved: (1) Preparation of Ba by hydrothermal method 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3; (2) Ba was prepared by the flow-through method. 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 tape and Mg2SiO4 tape; (3) will Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The O3 tape casting tape and the Mg2SiO4 tape casting tape are stacked in a sandwich structure and firstly hot pressed to obtain a ceramic thick film green body; (4) Sandwich multilayer high entropy lead-free dielectric materials are prepared by oscillating pressure sintering of ceramic thick film green bodies.
3. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 2, characterized in that: The steps of the hydrothermal method are: weighing raw material powders Ba(OH)2, Sr(OH)2, Na(OH)2, Bi(NO3)3, Ca(NO3)2, TiO2, Nb2O5, ZrO2, and MgO according to the stoichiometric ratio, dispersing and dissolving them in a solvent with an alkaline reagent and a morphology regulator, and then conducting a hydrothermal reaction.
4. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 2, characterized in that: The mass ratio of the raw material powder, alkaline reagent, morphology control agent and solvent is 1: (1-1.5): (1-1.5): (0.6-0.8), the alkaline reagent is sodium hydroxide; the morphology control agent is sodium citrate, sodium bicarbonate or polyvinyl alcohol; the solvent includes alcohol and water in a mass ratio of 1: (1-1.5).
5. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 150-185° C. and the time is 8-20 hours.
6. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 2, characterized in that: The flow-casting method for preparing Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The steps of O3 tape casting or Mg2SiO4 tape casting are as follows: 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 O3 or Mg2SiO4, an adhesive and a solvent II are mixed and ball-milled to obtain a high entropy medium casting slurry or a Mg2SiO4 casting slurry, which is then cast and dried to obtain the product.
7. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 6, characterized in that: The Ba 0.2 Sr 0.2 Na 0.2 Bi 0.2 Ca 0.2 Ti 0.25 Nb 0.25 Zr 0.25 Mg 0.25 The mass ratio of O3 or Mg2SiO4, adhesive and solvent II is 10:(2-5):(10-35).
8. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 7, characterized in that: The adhesive is Shenzhou No. Ⅲ adhesive or Lecell adhesive; the solvent II is anhydrous ethanol and toluene, or ethylene glycol and toluene.
9. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 2, characterized in that: The hot pressing temperature is 60-85° C., the pressure is 3-15 MPa, and the hot pressing time is 3-10 min.
10. The method for preparing the sandwich multilayer high entropy lead-free dielectric material according to claim 2, characterized in that: The oscillation pressure sintering method comprises the following steps: placing a ceramic thick film green body into an oscillation pressure sintering furnace, and when the temperature in the furnace is lower than 500° C., increasing the pressure in the furnace to 20-25 MPa, and keeping the temperature for 100-300 minutes; then increasing the temperature to 900-930° C., and starting to apply an oscillation pressure of 25-35 MPa on the basis of a pressure of 20-25 MPa, with an oscillation frequency of 1-3 Hz, and keeping the temperature for 20-30 minutes; then, under the same oscillation pressure, increasing the temperature to 1000-1050° C., keeping the temperature for 60-800 minutes, and obtaining a sandwich multilayer high entropy lead-free dielectric material after cooling.
Citation Information
Patent Citations
Sandwich-structured lead-free ceramic with low dielectric loss and high energy storage density and preparation method thereof
CN108623301A
Cited By
B-site doped perovskite dielectric layer material and preparation method thereof
CN121405467A
Pb (Mg1 / 2W1 / 2) (1-x) (In1 / 2Nb1 / 2) xO3-yMO based high-entropy multilayer ceramic material and preparation method thereof
CN122102691A